Effect of disinfectants on microorganisms and the structure of cement stone - Шкромада, О. І. (Scientific Progress & Innovations, 2012)
This article suggests disinfecting additive for construction materials that strengthen and improve the structure, preventing the growth and development of microflora: titanium dioxide (rutile) titanium anatase, red iron oxide pigment in pig enterprises. Carried out mycological studies of the samples and gave them a comparative evaluation. Fungicidal properties of building materials studied for 14–28 days. It was found that the samples with the addition of a disinfectant iron oxide pigment of fungal colonies decreased during this period.